Organizational involvement in CSR activities in the context of leaders' prosociality - Tomasz Szopiński; Katarzyna Bachnik; Oleg Gorbaniuk; Emilia Samardakiewicz-Kirol (Contemporary Economics, 2025)
This study investigates the influence of leaders' prosociality and attitudes toward corporate social responsibility (CSR) on organizational involvement in CSR activities, as well as the impact of CSR involvement on leaders' job satisfaction and organizational commitment. Despite extensive research on CSR's effect on employees' attitudes, the specific role of leaders' prosocial dispositions has been largely overlooked. Addressing this gap, the study focuses on leaders, recognizing their pivotal role in guiding organizational culture and CSR practices. Using a quantitative approach, data were collected from 132 managers across various companies through a structured survey comprising 25 items that measure prosociality, general CSR attitude, organizational CSR involvement, job satisfaction, and organizational commitment. The results indicate that leaders' positive attitudes towards CSR and prosocial behaviors significantly enhance organizational involvement in CSR activities. Moreover, organizational CSR involvement positively influences leaders' job satisfaction and commitment, mediated by their prosocial disposition. These findings underscore the importance of fostering prosocial values and a supportive CSR culture within organizations to strengthen leaders' engagement and attachment. The study recommends that organizations actively promote a prosocial culture and authentic CSR efforts to retain committed leaders, thereby enhancing the broader organizational commitment and morale. Further research should consider larger and more diverse samples to generalize these findings and explore additional internal factors influencing CSR outcomes.
Keywords: D22; D23; M14; 330; corporate social responsibility; prosociality; job satisfaction; leadership; organizational commitment